2004
DOI: 10.1590/s0004-28032004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação intra-operatória da pressão portal e resultados imediatos do tratamento cirúrgico da hipertensão portal em pacientes esquistossomóticos submetidos a desconexão ázigo-portal e esplenectomia

Abstract: These results have demonstrated that the esophagogastric devascularization with splenectomy promotes immediate decrease in the portal pressure and a consequent reduction in the esophageal varices size. We also observed that the risk of mortality and severe complications related to this technique is not insignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…EGDS reduces portal vein diameter and portal flow velocity leading to a decrease in the vein’s hyper flux component. This in turn reduces both diameter and number of esophagogastric varices [5, 10, 51–57]. Our study showed portal diameter decrease during the postoperative period, mirroring results of other studies.…”
Section: Discussionsupporting
confidence: 88%
“…EGDS reduces portal vein diameter and portal flow velocity leading to a decrease in the vein’s hyper flux component. This in turn reduces both diameter and number of esophagogastric varices [5, 10, 51–57]. Our study showed portal diameter decrease during the postoperative period, mirroring results of other studies.…”
Section: Discussionsupporting
confidence: 88%
“…Patients were divided into two groups, according to the portal pressure drop, in more or less than 30%.The threshold value of 30% was chosen because it was the average indicated by studies that measured the portal pressure before and after EGDS or splenectomy 4 , 7 , 11 , 22 .…”
Section: Methodsmentioning
confidence: 99%